(untitled) (Eurasian Journal of Learning and Academic Teaching, 2022)
In this article, the organizers of the school SPS,the professional theoretical and practical training of specialists in the field of conducting school SPS trainings, the results of monitoring the current situation for the organization of school sports are presented to your attention.